Between Illusion and Theatricality: Rosalind Krauss, Michael Fried and Minimalism - Friques(Universidade Federal do Estado do Rio de Janeiro – Rio de Janeiro/RJ, Brazil), Manoel Silvestre (Revista Brasileira de Estudos da Presença, 2022)
The article investigates Minimalism’s theatricality from the standpoint of Michael Fried’s and Rosalind Krauss’ critical readings. On the one hand, Krauss, from the very first moment in which she reflects on the works of Donald Judd and Dan Flavin, evidences their fundamental contradiction: the presence of the illusion, despite its rejection by the artists. On the other hand, Fried focuses on the alleged literalism of those projects, calling them theatricality. In the text, the two approaches will be confronted in order to explore the authors’ different views on the notion of theatricality.